PENGARUH PELAKSANAAN STRATEGI PEMASARAN TERHADAP MINAT PASIEN PADA RUMAH SAKIT SYAFIRA PEKANBARU - Riki Riduansyah Rambe; Meizy Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Strategy of Marketing is a series of goals and target, policies and rules that givedirection to effort marketing of company from time to time, in each generation and referenceand also its location, especially as response of company in the face of environmental changeand the state of competition. Interest of patients grow as a motive based on these attributesin accordance with the wishes and needs in using service, based on this, the company shouldbe appropriate to design a strategy of marketing to attract the interest of the consumersthemselves to be interested in the products of services offered, so that if consumers have aninterest in the product there will be decision to buy the product.This research was conducted at Hospital Syafira Pekanbaru. Lokated at JendralSudirman street, No. 134, Pekanbaru. The purpose of this Research was conducted todetermine the effect of the implementation of the marketing strategy of the interst of patient inHospitals of Syafira Pekanbaru.In this research, the methodology used is descriptive and quantitative with SPSSprogram, whice samples used were patient of Hospitals Syafira Pekanbaru and as source ofinformation is the HRD, Front of Office and Marketing manager. To determine the sampleusing the formula Slovin, method of sampling by accidental sampling. Techniques ofcollecting data is through interview, observation and quesioner.From the results analyse of data that includes the test of validity, reability, and simplelinear regression, implementation of marketing strategy in this research include both 7component of the product, price, place, promotion, people, process, physical environment.Each has indicators that are interrelated and positive effect on the interest of patiens inHospitals of Syafira Pekanbaru.Keyword: Marketing Strategy, Interest of Patient